2001
DOI: 10.1093/rheumatology/40.5.565
|View full text |Cite
|
Sign up to set email alerts
|

Anticardiolipin and anti‐β2 glycoprotein I antibodies in sera of 61 apparently healthy children at regular preventive visits

Abstract: This is the first report in which the cut-off values for aCL and anti-beta(2)GPI in children are expressed in concentrations of monoclonal antibodies. Low titres of aCL, which were identified frequently in apparently healthy children, were hypothesized to be the result of previous infections. The high mean value of IgG anti-beta(2)GPI observed in preschool children was an unexpected result of the study and might indicate a default response to nutritional exposure to beta(2)GPI in this age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
2
8

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 35 publications
3
64
2
8
Order By: Relevance
“…Our study results do not demonstrate an increased incidence of anticardiolipin antibodies, b2GP antibodies, anti-phosphatidylserine antibodies and anti-ethanolamine antibodies in ADHD children when compared to a similar group of healthy children. The percentage of children "positive" to the presence of anticardiolipin antibodies and b2GP antibodies in our study did not differ from that found in a healthy age matched population as studied by Avcin et al (2001). The prevalence of the other two antibodies (anti-ethanolamine and anti-phosphatidylserine) in a healthy population was not studied from a review of the recent literature.…”
Section: Discussioncontrasting
confidence: 74%
“…Our study results do not demonstrate an increased incidence of anticardiolipin antibodies, b2GP antibodies, anti-phosphatidylserine antibodies and anti-ethanolamine antibodies in ADHD children when compared to a similar group of healthy children. The percentage of children "positive" to the presence of anticardiolipin antibodies and b2GP antibodies in our study did not differ from that found in a healthy age matched population as studied by Avcin et al (2001). The prevalence of the other two antibodies (anti-ethanolamine and anti-phosphatidylserine) in a healthy population was not studied from a review of the recent literature.…”
Section: Discussioncontrasting
confidence: 74%
“…1). Unfortunately, no specific paediatric reference ranges for ab2-GP1 have been published and there are somewhat conflicting data on the prevalence of these antibodies in children compared with adults [1,11].…”
Section: Discussionmentioning
confidence: 99%
“…È quindi possibile che l'ingestione di b 2 GPI alimentare possa indurre nel bambino un'immunizzazione e quindi la produzione di anticorpi anti-b 2 GPI. Inoltre anche le infezioni virali e le vaccinazioni cui viene sottoposto il bambino durante il primo anno di vita possono indurre una risposta immune più o meno specifica, inclusa la produzione di anti-b 2 GPI (7,8). Per meglio definire le caratteristiche di anticorpi anti-b 2 GPI riscontrati in situazioni cliniche molto diverse tra loro, abbiamo valutato la fine specificità di questi anticorpi mediante l'utilizzo di kit ELISA sperimentali per la ricerca di anticorpi anti-D1 e anti-D4/5.…”
Section: Lavoro Originaleunclassified
“…Gli anti-b 2 GPI sono stati inoltre descritti in alcune condizioni non-autoimmuni come ad esempio nell'aterosclerosi (4) e nei pazienti con lebbra (5), e anche nei bambini con dermatite atopica (DA) (6). Si è trovato anche come bambini assolutamente sani, afferenti a visite di controllo preventive, possano mostrare positività per gli anti-b 2 GPI (7,8). Il fatto che la presenza di anti-b 2 GPI si possa associare ad uno spettro di condizioni così variegato che spazia da bambini assolutamente sani a pazienti con APS, potrebbe essere in parte spiegato dalla variabilità in termini di sensibilità e specificità tra le varie metodiche di laboratorio utilizzate (9).…”
unclassified